(untitled) (Educational Perspectives Magazine (REPED), 2023)
The aim of this article is to reveal the conclusions of a piece, of research in wich professional autobiographies were used to fínd out the needs of teacher trainees in the Specail Education Department at the Universidad Metropolitana de Ciencias de la Educación. The research was carried out in 2002 to 2003 and 14 female university teachers of the afore-mentioned Department participated in it. Likewise, the paper explains the reasons for selecting autobiographies as data collection tools to detect the needs for training, and at the same time, the main contributions are commented on made by autobiographies for professional development.